2023
DOI: 10.1093/mnras/stad1539
|View full text |Cite
|
Sign up to set email alerts
|

The C-Band All-Sky Survey (C-BASS): new constraints on the integrated radio spectrum of M 31

Abstract: The Andromeda galaxy (M 31) is our closest neighbouring spiral galaxy, making it an ideal target for studying the physics of the interstellar medium in a galaxy very similar to our own. Using new observations of M 31 at 4.76 GHz by the C-Band All-Sky Survey (C-BASS), and all available radio data at 1○ resolution, we produce the integrated spectrum and put new constraints on the synchrotron spectral index and anomalous microwave emission (AME) from M 31. We use aperture photometry and spectral modelling to fit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…However, more significant evidence supporting the presence of AME in M31 was subsequently confirmed by Battistelli et al (2019). A recent study by Harper et al (2023) reported the marginal detection of AME in M31, suggesting that it may not be uniformly distributed throughout the entire galaxy. Conversely, the study by Fernández-Torreiro et al (2024) presented a contrasting view, strongly advocating for the presence of AME in M31.…”
Section: Introductionmentioning
confidence: 91%
“…However, more significant evidence supporting the presence of AME in M31 was subsequently confirmed by Battistelli et al (2019). A recent study by Harper et al (2023) reported the marginal detection of AME in M31, suggesting that it may not be uniformly distributed throughout the entire galaxy. Conversely, the study by Fernández-Torreiro et al (2024) presented a contrasting view, strongly advocating for the presence of AME in M31.…”
Section: Introductionmentioning
confidence: 91%
“…Despite numerous radio surveys of M31 and local environs, there is no reported nonthermal emission in the SDSO area southeast of M31ʼs nucleus. In both low-and high-frequency radio and far-infrared surveys of M31, there has been no reported adjacent SNR or any evidence of emission in M31ʼs halo at SDSO's location so close to M31ʼs disk (Graeve et al 1981;Beck & Graeve 1982;Berkhuijsen et al 1983Berkhuijsen et al , 1991Beck et al 1998;Berkhuijsen et al 2003;Planck Collaboration et al 2015;Harper et al 2023). While SDSO's faint optical emission might suggest equally faint radio emission, the lack of any hint of coincident radio emission is a potential difficulty.…”
Section: A Faint Undiscovered Galactic Snrmentioning
confidence: 99%